A study to determine the protective effect of the aqueous extract of beta vulgaris and the drug hydroxyurea in female laboratory rats induced with hemolytic anemia - Muhaibis Awas, ayat; Hudhi Farhoud, Zainab (University of Thi-Qar Journal of agricultural research, 2025)
The study was conducted to investigate the effect of beta vulgaris extract and hydroxyurea on oxidative enzymes in laboratory female rats in which hemolytic anemia was induced using Phenylhydrazine. The groups were divided into seven groups, each group containing 5 females. The first control group was injected with distilled water, the second group was injected with Phenylhydrazine 0.1 mg/kg, the third group was injected with beetroot extract 100 mg/kg. The fourth group was injected with a mixture of beetroot extract and hydroxyurea, the fifth group was injected with Phenylhydrazine and injected with beetroot extract, the sixth group was injected with Phenylhydrazine and injected with hydroxyurea, the seventh group was injected with a mixture of hydroxyurea and injected with Phenylhydrazine and beetroot extract. Through statistical analysis of oxidative enzymes, the results showed an increase in the level of (Superoxide Dismutase) SOD enzyme in the fourth, sixth and seventh groups that were dosed with hydroxyurea compared to the control group, as well as an increase in the level of (Malondialdehyde)MDA enzyme in the fourth, sixth and seventh groups that were dosed with hydroxyurea. The results of the (Glutathion Peroxidase) GPX enzyme also showed no significant differences between the treatment groups at the probability level of P≤0.05. As for the (Catalase) CAT enzyme after 10 minutes, there was a significant increase in the second group compared to the control group and the rest of the treatment groups. The results also showed that the CAT enzyme after 30 minutes had a significant increase in the sixth group when compared to the control group. Conclusion: The study showed that the best group for inhibiting oxidative enzymes was the one that received the medical drug hydroxyurea.